Evaluation of insecticidal activity of diterpenes and lignans from Aristolochia malmeana against Anticarsia gemmatalis - Messiano, Gisele B. [UNESP]; Vieira, Leandro [UNESP]; Machado, Marcos B. [UNESP]; Lopes, Lucia Maria Xavier [UNESP]; De Bortoli, Sergio A. [UNESP]; Zukerman-Schpector, Julio (Amer Chemical Soc, 2008)
The insecticidal activity of hexane extracts from the roots and leaves of Aristolochia malmeana was evaluated against Anticarsia gemmatalis larvae by topical application. Extract from the roots was the most active and caused 50% mortality in larvae at 308.4 mu g/mu L. From this extract, a clerodane diterpene, (-)-kolavenic acid, and three lignans, (-)-kusunokinin, (-)-hinokinin, and (8S,8'R,9S)cubebin, were isolated by chromatography and partition procedures and then evaluated for their insecticidal activities either individually or in pairs. (-)-Kusunokinin showed higher activity against A. gemmatalis (LD10 = 9.3, LD50 = 230.1 mu g/mu L) than the crude extract, and its activity was dosedependent, whereas the other constituents did not exhibit any significant activity. Together with (-)kusunokinin and (-)-hinokinin, (-)-copalic acid, (-)-2-oxokolavenic acid, (-)-ent-6-beta-hydroxy-copalic acid, (8R,8'R,9R)- and (8R,8'R,9S)-cubebins, (-)-fargesin, and (-)-phillygenin were isolated from the hexane extract of the leaves. The compounds were identified on the basis of spectroscopic analysis.
Keywords: aristolochiaceae; Aristolochia malmeana; Anticarsia gemmatalls; insecticidal activity; lignan; diterpene; kusunokinin; cubebin; kolavenic acid; hinokinin